Pengaruh Literasi Keuangan dan Gaya Hidup terhadap Perilaku Pengelolaan Keuangan Mahasiswa Beasiswa KIP-Kuliah di Surabaya - Farra Fayza Wahyuningrum; Aminatuzzuhro Aminatuzzuhro (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
The purpose of this study is to analyze the influence of financial literacy and lifestyle on financial management among university students. The research method used in this study is quantitative. The population in this study were 988 students receiving KIP-Kuliah at universities in Surabaya, the class of 2021. The sample used in this study was 91 students, using a random sampling technique. The data used in this study were primary data, namely by distributing questionnaires. The data analysis technique used in this study was quantitative data analysis using statistical methods. The statistical method used was SmartPLS version 4.0. The results of the study indicate that financial literacy influences the financial management of KIP-Kuliah recipients at universities in Surabaya, class of 2021. Lifestyle has no influence on the financial management of KIP-Kuliah recipients at universities in Surabaya, class of 2021. Both financial literacy and lifestyle simultaneously influence the financial management of KIP-Kuliah recipients at universities in Surabaya, class of 2021